Calibration of a Three Meter Small Radio Telescope in Baghdad University using the Sun as a Reference Source - Hoobi, Mohammed R.; Abood, Kamal M. (Iraqi Journal of Science, 2019)
The calibration of the three meter Baghdad University Radio Telescope (BURT) has been performed using two types of calibrations: Antenna Position calibration, and Detector calibration. The sun is used as a reference source to calibrate the telescope. The antenna position Azimuth (Az), and Elevation (El) are calibrate according to sun’s azimuth and elevation in the date (11/10/2017; at time 10:19 AM). A calibration report is designed to illustrate the calibration parameters for each specific date and time. The detector calibration is representing a study for power spectrum response for the sun according to radio telescope frequency band (1.3 GHz – 1.5 GHz) with central frequency (1.42 GHz). Drift Scan function in the telescope’s software is used to draw the sun’s radio spectrum at date (23/1/2018; at time 09:57:25 AM).